Research on identifying pahs in vegetable oil produced from some plants in open environment. - Huy, Do Quang; Thanh, Le Nhu (VNU Journal of Science: Natural Sciences and Technology; Vol 20 No 1, 2004)
Some of vegetable oils were used  to  identify the Polycyclic Aromatic Hydrocarbons (PAHs). Contamination of PAHs in vegetable oils was due to technological processes or environmental sources. PAHs were detected in 3 vegetable oils, including raw coconut oil from Philippine, soya bean and olive- rapeseed oil from Vietnam. Concentration of PAHs was found in coconut oil, the maximum concentration was 22.048 |ig/kg. PAHs’ concentration in soya bean, olive-raspeseed oils was low, it was reduced during refining. Benzo(a)pyrene wasn’t detected in all samples, the maximum concentration of other PAHs was 10.640 ng/kg. PAHs concentration in raw vegetable oils were higher than refined oils.